(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The article describes the methodology of learning programming for students of various engineering disciplines (chemists, electricians, programmers, and mechatronics). Such courses as "Computer Training" and "Programming Languages", which are read at the Faculty of Computer-Science and Information Technology of Riga Technical University, are used as example. The purpose of these courses is to prepare specialists, who will be able effectively and without error to use computers in their future careers. The course structure depends on the specialty area in which students are studied. The course structure consists of three parts: the main (theoretical), laboratory and practical test. In this paper we show that for better development of the material is necessary to consider the solution of specific practical problems that may be encountered engineers particular profile, as well as providing current and final control of students.